CHARACTERIZATION AND STATIC MODELING OF BEKASAP RESERVOIR IN ZORAEL FIELD, CENTRAL SUMATRA BASIN - Erwin Permana, Rio
Zorael Field is a geological closure that is located in the southeastern part of the Central Sumatra Basin. This field was discovered in 1981 and production started in 1996. Production in this field comes from a single layer, the Bekasap formation, with an estimated recovery factor of 30%. Zorael Field has the potential to expand by over 50% recovery factor, as indicated by the surrounding field data. This research is necessary to provide a comprehensive understanding of the remaining hydrocarbon potential due to various drilling and well integrity issues that have caused inefficient reservoir drainage from existing wells. The study consists of several stages, including geological analysis (stratigraphy), geophysical analysis, petrophysical analysis, 3D static modeling, and reserve calculations. The stratigraphic analysis of the Bekasap formation, which is the hydrocarbon reservoir in this field, is interpreted as a tidal bar. facies deposited in a tide-dominated estuary environment during a transgressive phase. The parameters generated in petrophysical analysis include shale volume (Vsh), effective porosity (Phie), permeability (Perm), and effective water saturation (Sw). In order to complete a 3D static modeling, it is important to consider variables including shale volume, porosity, permeability, and irreducible water saturation. The initial stage involves modeling Vsh, distributed using a conceptual facies model used as input in variogram analysis. Phie and Swirr are modeled using sequential Gaussian simulation (SGS) and local variance mean (LVM) methods. Perm is calculated using multiple linear regression. In this study, fluid contacts are determined using petrophysical analysis and validated by dynamic reservoir history matching results. The deterministic reserve calculation is 9.46 million stock tank barrels (MMSTB). The probabilistic reserve calculation is done using predefined petrophysical uncertainty bounds, with a P50 result of 9.42 MMSTB. The reserve calculations from both methods are relatively close. Sensitivity analysis results indicate that Phie has the most significant impact on the oil volume calculation in the Zorael Field. According to this research, the Zorael Field has untapped development potential even though it has produced 3066 million barrels of oil to date.